The Effect of Production Costs and Consumer Demand on Upiya Karanji's Selling Price - Aurelia Revalina Anwar; Tri Handayani Amaliah; Ayu Rakhma Wuryandini (Majapahit Journal of Islamic Finance and Management, 2026)
This study aims to analyze the influence of production costs and consumer demand on the pricing for Upiya Karanji produced by artisans in Batu Layar Village, Bongomeme Subdistrict, Gorontalo Regency. Field conditions suggest that some artisans do not maintain systematic cost records and continue to set prices based on customary practices, while consumer demand fluctuates in response to seasonal factors and traditional ceremonial needs. The study employs a quantitative method with an associative approach. Primary data were collected through questionnaires distributed to 35 artisans, who were selected using purposive sampling. Data analysis included validity and reliability tests, classical assumption tests, multiple linear regression, t-tests, F-test, and the coefficient of determination, using SPSS as the analytical tool. The findings indicate that production costs have a positive and significant influence on the pricing, whereas consumer demand does not have a significant influence. However, simultaneously, both variables significantly influence pricing, as indicated by an F-count value of 19.541 > F-table of 3.28 and a significance level of 0.001 < 0.05.